ANALISIS PENDEKATAN BALANCE SCORECARD TERHADAP SASARAN STRATEGIS PERGURUAN TINGGI SWASTA - Elistia Elistia; Rojuaniah Rojuaniah; Siti Mariam (JURNAL LENTERA BISNIS, 2024)
Determining strategic targets for Private Higher Education (PHEI) has an impact on the growth and reputation of the organization, which is a key factor in the successful performance of private universities. One method of setting strategic targets can be to adopt the conceptual framework of the Balance Scorecard (BSC) perspective, namely the Internal Process Perspective, Customer Perspective, Learning and Growth Perspective, and Financial Perspective. Therefore, it is important to carry out this research to analyze the relevance of BSC adoption to the goals or targets of PHEI. The aim of this research is to analyze and explore the use of BSC in setting PHEI goals and objectives as a strategic management review. This research method uses a systematic, transparent, and replicable literature review to analyze the literature on the BSC concept. The research objects are 12 private universities in Indonesia that are accredited A and Superior. The results of the research show that of the 4 BSC perspectives that are most dominantly mentioned in the goals or objectives of PHEI, the Learning and Growth Perspective is mentioned 28 times, the Internal Process Perspective is mentioned 15 times, the Customer Perspective is mentioned 13 times, and the last is the Financial Perspective was mentioned 10 times. So, there are some PHEI that do not mention the Financial Perspective and Customer Perspective aspects of their strategic goals or objectives. Therefore, the findings of this research can be used as a future evaluation study of strategic targeting that adopts the BSC conceptual framework perspective. Keywords: Balance Scorecard, Private Higher Education, Internal Process Perspective, Customer Perspective, Learning and Growth Perspective, Financial Perspective